Sistem Pendukung Keputusan untuk Penentuan Investasi Cryptocurrency Menggunakan Metode Weighted Product - Saputra, Aldi Dwi; Akbar, Mutaqin (Journal of Informatics Management and Information Technology, 2025)
The rapid growth of cryptocurrencies with diverse characteristics poses challenges for investors, especially beginners, in selecting optimal investment options. This study seeks to construct and develop a decision support system (DSS) utilizing the Weighted Product (WP) technique to deliver objective recommendations for cryptocurrency investments. The evaluation criteria were determined through questionnaires distributed to investors, identifying five main criteria: asset liquidity, daily transaction volume, market capitalization, price volatility, and current cryptocurrency price. The system was developed using PHP, CSS, and JavaScript with Visual Studio Code as the development environment. The calculation results indicate that Bitcoin ranks first with a score of 0.058263, followed by Ethereum (0.05240), and Solana (0.044023). The developed system effectively generates cryptocurrency asset rankings by considering weights and values for each criterion, assisting users in making more accurate and optimal investment decisions.